SOCIO-LEGAL IMPLICATIONS OF ADOPTION: A STUDY ASBĀB AL-NUZŪL OF QS. AL-AḤZĀB VERSES 4–5 AND ITS RELATION TO HAḌANAH PRACTICES AT MUZDALIFAH ORPHANAGE, WARU SIDOARJO - Muhammad Dzikru Alfin Maulaya; Ahmad Yusam Thobroni (TAFASIR: Journal of Quranic Studies, 2025)
This Religion encourages its followers to engage in various forms of social worship, one of which is adopting children from underprivileged families as a means of alleviating their hardships. However, in practice, adoption is often carried out by altering the legal status of the adopted child to that of a biological one, which contradicts Islamic principles. This study aims to examine the socio-legal implications of QS al-Aḥzāb: 4–5, which emphasize the rectification of the concept of child adoption (tabannī) in Islam. These verses serve as the foundational basis for abolishing the pre-Islamic adoption system that equated adopted children with biological offspring. This research employs a library-based methodology with an asbāb al-nuzūl approach. The data are analyzed descriptively in relation to contemporary socio-religious phenomena. The findings indicate that Islam does not prohibit the practice of child care (ḥaḍānah), but restricts its legal consequences to ensure that it does not violate principles related to lineage, inheritance, and mahram relationships. The study also highlights the implementation of these values at Muzdalifah Orphanage in Waru, Sidoarjo, which applies an Islamic ḥaḍānah-based caregiving system providing affectionate care without altering the child’s original identity. The study concludes that QS al-Aḥzāb: 4–5 contain not only legal dimensions but also profound social values affirming the importance of compassion, justice, and responsibility in safeguarding children within modern society.